2021
DOI: 10.3390/mi12060630
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electrical Outputs of Piezoelectric Nanogenerators by Controlling the Dielectric Constant of ZnO/PDMS Composite

Abstract: Structural optimizations of the piezoelectric layer in nanogenerators have been predicted to enhance the output performance in terms of the figure of merit. Here, we report the effect of dielectric constant on electrical outputs of piezoelectric nanogenerator using ZnO/PDMS composites with varied ZnO coverages. The dielectric constant of piezoelectric layers was adjusted from 3.37 to 6.75. The electrical output voltage of 9 mV was achieved in the nanogenerator containing the ZnO/PDMS composite with the dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Finally, an SS-ZnONW nanogenerator, as a practical sensor power supply, achieved the detection of strain, light, and temperature signals, demonstrating its potential in low-consumption circuits, microsensing, and self-powered devices. Due to its deformation nature, multiple pulses were generated in one deformation cycle, leading to a wider frequency band than other reported methods. ,, Limited by the performance of the nanomanipulator (only manual operation, limited frequency, and working time), this paper only studies the working stability of the nanogenerator in a short time (63 min), and the plucking frequency is low. The relationship between the NWs’ deformation d and the corresponding acceleration has not been clarified, in whose field the generator would be applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, an SS-ZnONW nanogenerator, as a practical sensor power supply, achieved the detection of strain, light, and temperature signals, demonstrating its potential in low-consumption circuits, microsensing, and self-powered devices. Due to its deformation nature, multiple pulses were generated in one deformation cycle, leading to a wider frequency band than other reported methods. ,, Limited by the performance of the nanomanipulator (only manual operation, limited frequency, and working time), this paper only studies the working stability of the nanogenerator in a short time (63 min), and the plucking frequency is low. The relationship between the NWs’ deformation d and the corresponding acceleration has not been clarified, in whose field the generator would be applied.…”
Section: Resultsmentioning
confidence: 99%
“…The global energy crisis underscores the urgency to seek sustainable energy solutions, especially for micro- and nano-electronic devices. While researchers have explored thermoelectric nanogenerators based on pyroelectric materials to convert environmental waste heat energy into electrical energy, they typically achieve high output voltages but are constrained by specific applications. In parallel, mechanical vibration-based nanogenerators, such as triboelectric and piezoelectric nanogenerators, have shown potential by achieving open circuit voltages of tens of volts. However, the output of triboelectric nanogenerators is size-dependent, necessitating significant size and presenting fabrication complexities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dielectric constant of the piezoelectric layers was increased from 3.37 to 6.75 upon addition of ZnO to the ZnO/PDMS composite. 28 The high dielectric constant at 100 Hz is due to the interfacial polarization at the grain boundaries under the influence of low frequency. Exponential decay was observed in the value of the dielectric constant with an increase in the frequency, as the nano-dipoles are unable to align with the electric field as it varies.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO micro/nanowires have an instinctive bend ductility and highly efficient thermoelectricity, therefore it is crucial to explore the ZnO micro/nanowires for various applications with shape plasticity as well as application compatibility [6][7][8][9][10]. These micro/nanowires have also attracted a lot of interest owing to their unique semiconducting, photoelectric, and piezoelectric properties for plenty of applications in piezo-optoelectronics, such as nanogenerators [11][12][13][14][15], piezoelectric devices, etc., [16][17][18][19][20][21][22][23]. Most of the previous studies have reported that the crystal and electronic structure of the semiconductor nanowires are sensitive to the applied mechanical strain [24].…”
Section: Introductionmentioning
confidence: 99%